Blood Interferon-α Levels and Severity, Outcomes, and Inflammatory Profiles in Hospitalized COVID-19 Patients - Contoli, Marco; Papi, Alberto; Tomassetti, Luca; Rizzo, Paola; Vieceli Dalla Sega, Francesco; Fortini, Francesca; Torsani, Francesca; Morandi, Luca; Ronzoni, Luca; Zucchetti, Ottavio; Pavasini, Rita; Fogagnolo, Alberto; et al. (Frontiers in Immunology, 2021)
Background. Deficient interferon responses have been proposed as one of the relevant mechanisms prompting severe manifestations of COVID-19, Objective: To evaluate the interferon (IFN)-α levels in a cohort of COVID-19 patients in relation to severity, evolution of the clinical manifestations and immune/inflammatory profile. Methods. This is prospective study recruiting consecutive hospitalized patients with respiratory failure associated with SARS-COV2 infection and matched controls. After enrollment, patients were assessed every 7±2 days for additional 2 consecutive visits, for a total of 21 days. The severity of the clinical condition was ranked based on the level of respiratory support required. At each time-point blood samples were obtained to assess immune cells and mediators by multiplex immunoassay. Results. Fifty-four COVD-19 and 11 control patients matched for severity were enrolled. At recruitment, lower levels of blood IFN-α were found in COVID-19 patients compared to controls (3.8-fold difference, p<0.01). Improvements in COVID-19 severity were paralleled by a significant increase of blood IFN-α levels. A significant increase in blood IFN-α was found over the study period in survivors (70% of the study population). A similar trend was found for blood IFN-β with IFN-β levels below the threshold of detectability in a substantial proportion of subjects. Significantly higher values of blood lymphocytes and lower levels of IL-10 were found at each time point in patients who survived compared to patients who died. In patients who clinically improved and survived during the study, we found an inverse association between IL-10 and IFN-α levels Conclusion. The study identifies a blood immune profile defined by deficient IFN-α levels associated with increased IL-10 expression in patients progressing to severe/life threatening COVID-19 conditions, suggesting the involvement of immunological pathways that could be target of pharmacological intervention